Evaluation of Paramedical Student’s Knowledge on COVID-19: A Comparative Study - Yadav, Khushbu; Prakash, Satyam; Yadav, Basant Kumar; Pokhrel, Bishal (Janaki Medical College Journal of Medical Science, 2023)
Background & Objectives: The COVID-19 pandemic has presented the world community with its greatest challenges so far. Paramedics play a crucial role in providing pre-hospital care to patients who require urgent medical attention in clinical settings. Therefore, the aim of the study was to evaluate the knowledge on COVID-19 among health assistant (HA) students studying in different paramedical colleges in Janakpurdham. Material and Methods: A descriptive cross-sectional study was performed utilizing a structured questionnaire to acquire responses from HA Students studying in different colleges of Janakpurdham in the months of April and May 2022. Descriptive analysis was applied to calculate the frequencies and proportions. A p-value less than 0.05 were considered as significant. Results: Out of total 360 students, 280 were enrolled. The majority of students were under 20 years old. All of the students were aware of the COVID-19 infection at National Human Resource Development Academy (NHRDA) and Mithila Technical Academy (MTA) colleges, with the exception of 3.61% Care Medical Center (CMC) students. A large percentage of students (52.80% boys , 47.19% girls) responded that the respiratory tract is the primary route by which COVID-19 infections are spread, followed by the students from NHRDA and CMC. Most of the students from all colleges received satisfactory scores on the COVID-19 knowledge test. There was negative association of score of knowledge between 1st, 2nd and 3rd year students of CMC and MTA (p=0.96 and p=0.11) respectively. However, there was positive association of score of knowledge between 1st, 2nd and 3rd year NHRDA students (p=0.01). Conclusion: The majority of college students studying at different colleges had satisfactory knowledge, while a moderate number of students had poor and just a few had good knowledge scores on the COVID-19. In order to increase knowledge, various kinds of strategies, regulations, and initiatives should be accomplished and implemented effectively throughout the lower to higher level education.